Dicyanopyrazine-derived push–pull chromophores for highly efficient photoredox catalysis - Zhao, Yu; Zhang, Chenhao; Foo Chin, Kek; Pytela, Oldřich; Wei, Guo; Liu, Hongjun; Bureš, Filip; Zhiyong, Jiang (Royal Society of Chemistry, 2014)
Here, we report dicyanopyrazine (DPZ)-derived push–pull chromophores, easily prepared and tunable organic compounds, as new kinds of photoredox catalysts. In particular, the DPZ derivative H, containing 2-methoxythienyl as electron-donating moiety, exhibits a broad absorption of visible light with an absorption edge up to 500 nm and excellent redox properties, and has been demonstrated as a desirably active and efficient photoredox catalyst in four challenging kinds of photoredox reactions. The amount of catalyst in most reactions is less than 0.1 mol% and even 0.01 mol%, representing the lowest catalyst loading in the current photoredox organocatalysis.